How xenocentrism shapes online consumer behavior: psychographic drivers of foreign brand preference - Hahn, Ivanete Schneider; Polawski, Thais Cofferi; Fertig, Mariléia Batista (Revista de Administração da UFSM, 2025)
Purpose: Xenocentrism, the tendency to prefer foreign brands over domestic ones, is prevalent in emerging markets such as Brazil and China. However, few studies have examined its determinants and impact on e-commerce. This study investigates the influence of xenocentrism on online purchase intentions, analyzing how product quality perception, country-of-origin image, purchasing power, status consumption, and social mobility aspirations shape this behavior. Design/methodology: A survey of 311 e-commerce consumers was conducted, and linear regression analysis was carried out. Findings: The analysis confirmed that higher xenocentrism is associated with greater purchase intentions for foreign brands. Psychographic characteristics such as status consumption, perceived inferiority, and brand image significantly contribute to this phenomenon. Research implications: The findings expand the literature on digital consumer behavior, providing strategic insights for global brands and e-commerce platforms. Originality/value: The study highlights the importance of brand positioning, global identity construction, and leveraging psychographic attributes to attract xenocentric consumers.